2012
DOI: 10.1166/jnn.2012.6175
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of <I>Shewanella Loihica</I> PV-4 on Gold Nanoparticles-Modified Boron-Doped Diamond Electrodes Fabricated by Layer-by-Layer Technique

Abstract: Microbial Fuel Cells (MFCs) are robust devices capable of taping biological energy, converting pollutants into electricity through renewable biomass. The fabrication of nanostructured electrodes with good bio- and electrochemical activity, play a profound role in promoting power generation of MFCs. Au nanoparticles (AuNPs)-modified Boron-Doped Diamond (BDD) electrodes are fabricated by layer-by-layer (LBL) self-assembly technique and used for the direct electrochemistry of Shewanella loihica PV-4 in an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
3
8
1
Order By: Relevance
“…Energies 2017, 10, x FOR PEER REVIEW 7 of 16 performance. These results were similar to reported results that the current density generated by S. loihica PV-4 was improved on the (Au/PAH)4/BDD electrode [37], (Fe2O3/CS)4/ITO electrode [38] and ITO/(PAH/GE)2 electrode [35] due to the appropriate amount of Au nanoparticles, Fe2O3 nanorods, graphene and thickness of PAH and chitosan. However, with respect to the current densities generated on other electrode materials-such as the (CNTs/PANI)12/APTES/ITO electrode (70.3 mA/m 2 ) [36], graphite electrode (585 mA/m 2 ) and CNT-coated graphite electrode (1429 mA/m 2 ) [26]that of the (CNTs/PAH)9-ITO electrode was unsatisfied, probably due to the increase of electron's pathway distance between microbe and electrode, caused by the insulated PAH.…”
Section: Chronoamperometric Resultssupporting
confidence: 91%
“…Energies 2017, 10, x FOR PEER REVIEW 7 of 16 performance. These results were similar to reported results that the current density generated by S. loihica PV-4 was improved on the (Au/PAH)4/BDD electrode [37], (Fe2O3/CS)4/ITO electrode [38] and ITO/(PAH/GE)2 electrode [35] due to the appropriate amount of Au nanoparticles, Fe2O3 nanorods, graphene and thickness of PAH and chitosan. However, with respect to the current densities generated on other electrode materials-such as the (CNTs/PANI)12/APTES/ITO electrode (70.3 mA/m 2 ) [36], graphite electrode (585 mA/m 2 ) and CNT-coated graphite electrode (1429 mA/m 2 ) [26]that of the (CNTs/PAH)9-ITO electrode was unsatisfied, probably due to the increase of electron's pathway distance between microbe and electrode, caused by the insulated PAH.…”
Section: Chronoamperometric Resultssupporting
confidence: 91%
“…In mice, intravenous injection of 50 nm NDs led to long-term entrapment in the liver and the lung [195], but no mice showed any abnormal symptoms. Similarly, subcutaneous and intraperitoneal injection of 100 nm NDs in rats led to accumulation of NDs in retention organs over 1 month with no impact on the rats' viability [197]. However, a slight surface-dependent genotoxicity of NDs was recently reported on embryonic stem cells [199].…”
Section: Nds Toxicity and Biodistributionmentioning
confidence: 99%
“…Several long-term in vitro [22,194] and in vivo [195][196][197] previous studies demonstrated that NDs are non-cytotoxic, better tolerated by cells than other nanocarbon materials [198]. NDs introduced into Caenorhabditis elegans worm did not cause any detectable stress to worms [198].…”
Section: Nds Toxicity and Biodistributionmentioning
confidence: 99%
See 2 more Smart Citations